DOES THE PRESCRIPTION ACT APPLY TO CLAIMS UNDER THE LABOUR RELATIONS ACT? - Chuks Okpaluba; M Budeli-Nemakonde (Obiter, 2022)
The applicability or otherwise of the Prescription Act 68 of 1969 to claims under the Labour Relations Act 66 of 1995 (LRA) is a hot topic in contemporary labour law. In particular, questions as to whether an arbitration award, an unfairly dismissed employee’s claim, an order of reinstatement, or a claim for arrear wages could be thrown out of court for having prescribed have been encountered in at least four recent decisions of the Constitutional Court of South Africa – Myathaza v JHB Metropolitan Bus Service (SOC) Ltd t/a Bus Metrobus 2018 (1) SA 38 (CC); Mogaila v Coca-Cola Fortune (Pty) Ltd 2018 (1) SA 82 (CC); FAWU obo Gaoshubelwe v Pieman’s Pantry (Pty) Ltd (2018) 39 ILJ 1213 (CC); and NUMSA obo Fohlisa v Hendor Mining Supplies (A Division of Marschalk Beleggings) (Pty) Ltd (2017) 38 ILJ 1560 (CC). Given the environment in which labour disputes take place, and that expedition is of the essence in a regulated dispute resolution process, one could conceive of a reinstatement claim arising from a labour dispute being caught by the general limitation on lodging civil claims after three years. The rationale for limiting the period during which civil claims may be made ought, mutatis mutandis, also to apply to matters arising from employment claims – especially if it is borne in mind that expedition is at the heart of the settlement of labour disputes. In the absence of any mention of a time-bar for laying reinstatement claims under the LRA (except for the 30 days for referring a dispute of unfair dismissal or 90 days for unfair labour practice to a bargaining council or the Commission for Conciliation, Mediation and Arbitration (CCMA) (s 191)), it is not surprising that the applicability or otherwise of the prescription period of three years has been in issue in a number of reinstatement claims.